G165 Female genital mutilation in London and the UNICEF report; a local perspective on worldwide statistics. (7th April 2014) - Hodes, D; Armitage, A; Dykes, A
Abstract : Background: In July 2013 the UNICEF report stated that 125 million women worldwide are affected by female genital mutilation (FGM). Despite an estimated 20, 000 children at risk in the UK there is a complete absence of data on presentation in childhood and ignorance among many healthcare workers. Although, since 2003, it is illegal to take a child out of the country for FGM, there have been no prosecutions. Aims: To increase understanding of FGM by collecting and analysing details of all paediatric presentations of suspected FGM to a London clinic from 2006 onwards. Methods: Retrospective data collection on all suspected FGM cases referred to the tertiary safeguarding clinic in an inner London teaching hospital from 2006, including details of referral, history and examination findings. Results: Of 32 referrals 13 (41%) were since the start of 2013. 26 were Somali, 5 Ethiopian and 1 Malay. Common routes of referral included: healthcare workers (7), school concerns (7), siblings of cases (4) and family disputes (5). 22 (69%) were confirmed to have had FGM. Of the 22 with FGM 15 were examined, of whom none had undergone WHO type 3 FGM (infundibulation). 10 girls (60%) had a normal or near normal examination (WHO type 4) with 5 (40%) having WHO types 1 and 2. Four children were taken from the UK after 2003 (i.e. illegally); unclear perpetrators and a lack of evidence have prevented prosecutions. Conclusions: Physical signs of FGM may be subtle and a normal examination does not exclude it. Our findings support the limited evidence from UNICEF that there is a trend toward less severe forms of FGM. WHO Type 4 without anatomical change was the commonest category in this small cohort and hence use of a revised classification (UNICEF) reflecting current practices could improve understanding of FGM and its implications for the child. Pursuing prosecution for neglect, as opposed to FGM, might be more successful in protecting children. The observed increase in referrals in 2013 supports the success of recent awareness campaigns and increases the chances of a criminal prosecution in this country.